Retinal vascular changes in congenital hypertrophy of the retinal pigment epithelium. - Cleary, P. E. (1976)
The overlying retinal blood vessels were abnormal in five cases of congenital hypertrophy of the retinal pigment epithelium. This illustrated the well-recognized association between outer retinal degeneration and obliteration of the overlying retinal vasculature. The proposed pathophysiological mechanisms, however, seem inadequate to explain completely the morphological changes of the retinal blood vessels in the presence of atrophy of the outer retina.